Profiles and Predictors of Infant Sleep Problems Across the First Year. Issue 2 (February 2020) - Cook, Fallon; Conway, Laura; Gartland, Deirdre; Giallo, Rebecca; Keys, Elizabeth; Brown, Stephanie
ABSTRACT: Objective: To identify profiles and predictors of maternal-reported infant sleep problems across the first postnatal year. Methods: Survey data examining maternal mental and physical health, intimate partner violence (IPV), and infant sleep problems and night waking were gathered from a cohort of 1, 460 nulliparous women at 15 weeks' gestation and when their infants were 3, 6, 9, and 12 months old. Results: Latent class analysis revealed 5 profiles of infant sleep problems, including those who had few problems (24.7%), persistent moderate problems (27.3%), increased problems at 6 months (10.8%), increased problems at 9 months (17.8%), and persistent severe problems (19.4%). Persistent severe infant sleep problems were associated with prepartum and postpartum maternal depression (adjusted odds ratio [AOR] 2.13, 95% confidence interval [CI] 1.35–3.34, p < 0.01; AOR 2.52, 95% CI 1.64–3.87, p < 0.001, respectively), poorer prepartum and postpartum perception of health (adjusted mean difference [AMD] 23.48, 95% CI 24.9 to 22.1, p < 0.01; AMD 23.78, 95% CI 25.2 to 22.4, p < 0.001, respectively), increased postpartum anxiety (AOR 2.22, 95% CI 1.26–3.90, p < 0.01), and increased prevalence of IPV in the first year postpartum (AOR 1.86, 95% CI 1.20–2.87, p < 0.01). Conclusion: Poorer prepartum and postpartum maternal mental and physical health, and IPV, were associated with maternal report of persistent severe infant sleep problems. Women experiencing prenatal physical and mental health difficulties may benefit from advice on managing infant sleep and settling. Health professionals working with unsettled infants must be equipped to enquire about and respond appropriately to disclosures of IPV. Abstract : This article has supplementary material on the web site: www.jdbp.org.